Addition of Anadara Granosa Shell Chitosan in Production Bioplastics - Rhenny Ratnawati; Sri Widyastuti; Yitno Utomo; Diana Evawati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Bioplastics is a plastic composite material that can decompose quickly and is environmentally friendly when interacting with soil and microorganisms. The aims of the research are: to examine the optimal composition of bioplastics made from tapioca waste by adding blood clam shell chitosan and glycerol, to determine the quality of production bioplastics from tapioca waste with the addition of blood clam shell chitosan and glycerol, and to determine the chemical content of the clam shells. bioplastic function of tapioca with the addition of blood clam shell chitosan and glycerol. The method used is experimental. Production of bioplastic by mixing waste tapioca flour, chitosan, and glycerol with a composition of 65%:35%:5mL, 70%:30%:5mL, and 75%:25%:5mL and additional water. The sample was put into a water bath and stirred at a temperature of 80oC for 15 minutes. Bioplastics were printed in aluminum foil, dried at 100oC for 90 minutes and cooled at room temperature for 6 hours. Laboratory test samples with tensile strength, elongation at break, FTIR, and biodegradation tests according to SNI 7188.7:2016 in the category of bioplastic easily decomposed. The results of the tensile strength on PBA1 samples were 0.75 Mpa, PBA2 samples were 0.54 Mpa, and PBA3 samples were 0.34 Mpa. Test value for elongation at break the PBA1 sample is 23.68%, the PBA2 sample is 15.33%, and the PBA3 sample is 12.12%. The sample test results do not meet the quality standard value of SNI 7188.7:2016 for the bioplastic category. The optimal composition of bioplastics is found in the PBA2 sample using tapioca flour as raw material with chitosan and glycerol as much as 70%:30%:5mL with a tensile strength 0.54%, an elongation at break 15.33%, biodegradation of 43%, and has a bioplastic content with functional groups (C=C), (CO), (CH),(OH), (C=C), and (CH2)n in the FTIR test results.